1998
DOI: 10.1016/s0895-7061(97)00486-x
|View full text |Cite
|
Sign up to set email alerts
|

No Association Between α-Adducin 460 Polymorphism and Essential Hypertension in a Japanese Population

Abstract: Many unknown genetic factors are involved in the pathogenesis of hypertension. Recently, the reverse genetic approach revealed that some genetic variants, such as angiotensinogen, lipoprotein lipase, and alpha-adducin gene polymorphisms, increase the risk for hypertension. Both in rat and human, the genetic predisposition to hypertension was confirmed only for angiotensinogen and alpha-adducin genes. Adducin is a membrane cytoskeletal protein, which is thought to regulate sodium transport. Abnormalities of mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
40
3
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 19 publications
8
40
3
1
Order By: Relevance
“…6,7 Despite these persuasive physiologic links, several other studies, like this one, have failed to find an association between the variant allele of ␣-adducin and hypertension in Anglo-Australians 8 and in Japanese patients. 3,9,10 The ␣-adducin polymorphism may be in linkage disequilibrium with other mutations that are responsible for salt sensitivity or the risk of hypertension.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 Despite these persuasive physiologic links, several other studies, like this one, have failed to find an association between the variant allele of ␣-adducin and hypertension in Anglo-Australians 8 and in Japanese patients. 3,9,10 The ␣-adducin polymorphism may be in linkage disequilibrium with other mutations that are responsible for salt sensitivity or the risk of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…2 Blood pressure responses to acute salt-sensitivity tests and to chronic diuretic therapy were more pronounced in heterozygotes than in wild-type homozygotes. 2 In a Japanese population, however, the ␣-adducin polymorphism was not associated with hypertension 3 even though the phenotype of salt-sensitivity has been associated with an increased risk of cardiovascular events among Japanese patients with essential hypertension. 4 Using data from a large Dutch case-control study of myocardial infarction, 5 we examined the associations of the ␣-adducin polymorphism with level of blood pressure and risk of myocardial infarction.…”
Section: Introductionmentioning
confidence: 94%
“…These huge BP variability differences were partly attributed to heterogeneity of human disease. 6,7 Although some studies 3,5,[8][9][10][11] have found a positive association between polymorphic variants of the ␣-adducin gene and hypertension, others 1,12,13 have failed to reveal any significant association. Importantly, no published studies have focused on isolated systolic hypertension (ISH) patients or the elderly.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Despite the several earlier reports, later studies on the association between these polymorphisms and hypertension reported conflicting results. [3][4][5][6][7][8] Studies in the Japanese population on the association between these salt-sensitivity related gene polymorphisms and hypertension may warrant special attention. Salt consumption by the Japanese is relatively high compared to other populations 9 and also they have a higher 235T allele frequency than M of the angiotensinogen M235T polymorphism, the former has been related to hypertension.…”
mentioning
confidence: 99%
“…However, studies in the Japanese are inconclusive, probably due to the relatively small number of subjects, up to about 1200, per study, and the ignoring of confounding factors, such as body mass index (BMI). [4][5][6][7] Thus, we studied the association between these polymorphisms and hypertension on a large-scale general population in Japan.…”
mentioning
confidence: 99%